Model Pembelajaran STAD Berbantuan Media Scrapbook Untuk Meningkatkan Hasil Belajar Siswa Sekolah Dasar - Vita Apriliya; Mohammad Kanzunnudin; Imaniar Purbasari (Universitas Pendidikan Indonesia Kampus Serang, 2020)
This study aimed to improve students’ learning outcomes through the STAD model aided by Scrapbook media in theme 7